In silico study of the encapsulation of α-tocopherol and α-tocotrienol vitamins E into cucurbit[7]uril - Edilino de Lima, Felipe; Giordano Viegas, Rafael [UNESP]; Vital de Oliveira, Osmair (Elsevier, 2023)
Theoretical methods were used to investigate the encapsulation of two vitamin E isoforms, α-tocopherol (α-TOC) and α-tocotrienol (α-TCT), into the macrocycle cucurbit[7]uril (CB[7]). The vitamins@CB[7] complexes were stable along 100 ns molecular dynamics simulation with similar conformation. The binding free energy obtained from the MM/PBSA method is ∼ –25 kcal.mol−1 for both complexes. Also, DFT-D3/B3LYP/6-31G(d,p) calculations indicate a favorable encapsulation process with bind energies of –58.25 (α-TOC@CB[7]) and –61.08 kcal.mol−1 (α-TCT@CB[7]). Moreover, the calculated solvation enthalpies show a solubility enhancement of complexed vitamins compared to their free forms. Finally, CB[7] may be a promising macrocyclic host for encapsulating vitamins E.
Keywords: Cucurbit[7]uril; Drug delivery; Theoretical methods; Vitamins E